Sois femme et tais-toi: the search for subjectivity through revolt in Marie Cardinal‘s Les Mots pour le dire - McGivern, Mary (Kansas State University, 2009)
Much of the critical work on Marie Cardinal's Les Mots pour le dire has focused primarily on the hysteria of the novel‘s narrator and her subsequent journey through psychoanalysis. More recently, research on the novel has expanded to include the issues of the narrator‘s pied-noir identity, nostalgia and memory. While such criticisms shed light on the intent of the novel, they do not necessarily explain the enigmatic and oftentimes overlooked final line of the text: "Quelques jour plus tard c‘était Mai 1968." In this thesis, I propose that this line is the key to understanding the novel; as such, I seek to re-examine Les Mots pour le dire through a feminist lens in order to explicate the seemingly malapropos reference to May 1968 and use it to explain central elements of the novel, including the narrator‘s madness, her tumultuous mother-daughter relationship and her eventual authorship. That the events of May 1968 represent one of the most subversive and socially destructive periods in recent French history as well as a giant shift towards the moral left establishes the value of revolt in Les Mots pour le dire. Specifically, I argue that Cardinal attacks the collusion of the ballasts of patriarchal society, religion, capitalism and class, and how these institutions have profited from the subjugation of women in society. When viewed in this light, the narrator‘s madness cannot simply be the product of her mother‘s psychological abuses. Instead, her madness and subsequent detachment from society symbolize the ultimate rejection of a world in which she finds herself oppressed and manipulated. She thus emerges not as a woman consumed by insanity but as a woman in revolt.
Keywords: Marie Cardinal; madness; revolt; writing; family; couple; Literature, General (0401)